Studi Komparasi: Produksi Bioetanol Nira Batang Kelapa Sawit oleh Flokulan dan Non- Flokulan Saccharomyces cerevisiae - Kafidul Ulum; Indria Purwantiningrum; Retno Dwi Yustina; Untung Murdiyatmo; Agustin Krisna Wardani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Two types of yeast were used for bioethanol production from oil palm trunk sap, the flocculant Saccharomyces cerevisiae NCYC1195 and nonflocculant Saccharomyces cerevisiae Kyokai 7 (NCYC-479). Flocculant Saccharomyces cerevisiae is yeast that has ability to aggregate into flocks which precipitate rapidly in culture medium. The effect of urea as a nitrogen source was also investigated in this study. Some concentrations of urea were added i.e. 0%, 0.1%, 0.2%, and 0.3% (w/v) during fermentation. The purpose of this study is to obtain the best condition by strain of Saccharomyces cerevisiae and urea concentration for the highest ethanol production. The highest ethanol production and yield was obtained at 4.86% (v/v) and 0.52 (g/g) respectively, by nonflocculant Saccharomyces cerevisiae Kyokai 7 (NCYC-479) without the addition of urea.